1988
DOI: 10.1126/science.3276005
|View full text |Cite
|
Sign up to set email alerts
|

A 13-Kilodalton Maize Mitochondrial Protein in E. coli Confers Sensitivity to Bipolaris maydis Toxin

Abstract: The Texas male-sterile cytoplasm (cms-T) of maize carries the cytoplasmically inherited trait of male sterility. Mitochondria isolated from cms-T maize are specifically sensitive to a toxin (BmT-toxin) produced by the fungal pathogen Bipolaris maydis, race T, and the carbamate insecticide methomyl. A mitochondrial gene unique to cms-T maize, which produces a 13-kilodalton polypeptide associated with cytoplasmic male sterility, was expressed in Escherichia coli. After addition of BmT-toxin or methomyl, inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
4

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(112 citation statements)
references
References 20 publications
5
102
0
4
Order By: Relevance
“…feature is distinct from that of the common bean (Phaseolus vulgaris) CMS gene orf239, which results in sporophytic male sterility in transgenic tobacco plants (He et al, 1996). It was previously shown that the maize CMS-T gene urf13 also encodes a cytotoxic peptide (Dewey et al, 1988). In addition, the expression of CMS-associated genes orf552 from sunflower (Helianthus annuus) and orf138 from radish were also lethal to E. coli (Nakai et al, 1995;Duroc et al, 2005;Y.-G. Liu, unpublished data).…”
Section: Discussion Abnormal Mitochondrial Orfs and Cmsmentioning
confidence: 99%
“…feature is distinct from that of the common bean (Phaseolus vulgaris) CMS gene orf239, which results in sporophytic male sterility in transgenic tobacco plants (He et al, 1996). It was previously shown that the maize CMS-T gene urf13 also encodes a cytotoxic peptide (Dewey et al, 1988). In addition, the expression of CMS-associated genes orf552 from sunflower (Helianthus annuus) and orf138 from radish were also lethal to E. coli (Nakai et al, 1995;Duroc et al, 2005;Y.-G. Liu, unpublished data).…”
Section: Discussion Abnormal Mitochondrial Orfs and Cmsmentioning
confidence: 99%
“…These properties help to explain its known biological activity. T-URFl 3 confers sensitivity to fungal toxins (BmT and Pm) and to methomyl when the gene coding for it is expressed in E. coli (5,10), and also confers sensitivity on yeast cells, provided that it is targeted to mitochondria (20). Both toxins and methomyl dissipate the membrane potential of mitochondria and cause leakage of ions.…”
Section: Discussionmentioning
confidence: 99%
“…The grids, with section side down, were floated on drops of the solutions placed on the Parafilm. The sections were preincubated for 10 …”
Section: Immunolabelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The most extensively analyzed CMS system is probably the CMS-T maize. In CMS-T, mitochondrial chimeric gene T-urf13 encodes a 13 kDa polypeptide (URF13) which strongly inhibits E. coli growth [6]. A few other CMS-associated genes (sunflower orf522, Brassica Ogura radish orf138 and BT-rice orf79) have also been shown to encode the toxic protein [7]- [9].…”
Section: Cms-associated Chimeric Orfs Are Often Toxicmentioning
confidence: 99%